ANALYSIS OF TASK-ORIENTED LEADERSHIP BEHAVIOR IN ENHANCING ORGANIZATIONAL EFFECTIVENESS OF EDUCATIONAL INSTITUTIONS (A CASE STUDY AT MTSN 1 TULUNGAGUNG) - Musalam; Prim Masrokan Mutohar; Imam Fuadi (International Journal of Multidisciplinary Reseach, 2025)
Education serves as a fundamental pillar in developing human resources and enhancing national competitiveness, including through madrasahs as Islamic educational institutions that not only transfer knowledge but also shape students’ character and spirituality. This study aims to analyze the task-oriented leadership behavior of the principal at MTsN 1 Tulungagung and its impact on organizational effectiveness, as well as to identify the challenges and strategies in its implementation. The research focuses on how the principal plans, distributes responsibilities, supervises, and evaluates the performance of teachers and staff. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, participatory observation, and examination of official madrasah documents. Data validity was ensured through triangulation of methods and sources, while analysis was conducted interactively through data reduction, presentation, and conclusion drawing. The findings indicate that task-oriented leadership at MTsN 1 Tulungagung enhances organizational structural efficiency, academic quality, and administrative accountability. The principal emphasizes strategic planning, proportional task allocation, routine supervision, and continuous evaluation, ensuring that all educational processes run effectively and align with the institution’s vision. This approach not only strengthens productivity and work discipline but also integrates Islamic spiritual and ethical values, such as amanah (trustworthiness), ihsan (excellence), and justice, into every organizational activity. The study confirms that task-oriented leadership can serve as an effective strategy to improve the institutional quality of madrasahs, provided it is balanced with attention to social relationships and member well-being.